Representasi Trauma Tokoh ’Karang’ pada Novel Aku Tak Membenci Hujan Karya Sri Puji Hartini dalam Perspektif Cathy Caruth - Lidya Nurmalawati; Tristanti Apriyani (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Psychological trauma is an important theme in literary works because it reflects complex emotional experiences and influences the formation of a character’s identity. One literary work that portrays such experiences is the novel Aku Tak Membenci Hujan by Sri Puji Hartini, which depicts the character Karang who experiences violence and rejection since childhood. This study aims to analyze the representation of trauma experienced by Karang using Cathy Caruth’s trauma theory. This research employs a qualitative descriptive method with a literary psychology approach. The data source is the novel Aku Tak Membenci Hujan, while the data consist of narrative quotations, dialogues, and depictions of inner conflicts that indicate traumatic symptoms. Data were collected through reading and note-taking techniques and analyzed by relating textual findings to the main concepts of Cathy Caruth’s trauma theory. The results show that Karang’s trauma is represented in three main forms: trauma as an experience that is not fully realized when it occurs, trauma that reappears through repetitive behaviors and emotional responses, and trauma represented through narrative fragmentation. These findings indicate that trauma in literary works not only functions as a background of the character’s experience but also shapes identity and the development of the narrative structure.